Strategi Kesantunan Positif Tuturan Mahasiswa Bahasa dan Sastra Arab UIN Imam Bonjol Padang - Adjie Prasetio Utama (Diwan: Jurnal Bahasa dan Sastra Arab, 2019)
This paper discusses the patterns and strategies of the Arabic Language and Literature Department of the Faculty of Adab and Humanities in developing language politeness in the lecture process. The author collects data from the lecture process (presentation of papers and questions and answers) of Naqd Adabi II course which is carried out by students of class 2014. Data is collected using record and note techniques, analyzed by referring to the theory of positive politeness expressed in pragmatics. It can be concluded that the positive politeness strategy used by the UIN IB Padang Arabic Language and Literature students is as follows: (1) using group identity markers using specifically 'we' and 'BSA students' expressions; (2) Exaggerating the attention, approval, and sympathy to the opponent's speech by using the phrase 'extraordinary' and 'indeed reaching to the core of the problem' as an appreciation to the opponents of speech; (3) Avoiding disagreement by pretending to agree, pseudo agreement, cheating for good (white lies), and hedging opinions by using a fenced phrase 'on one side' and contradicting the agreement he had expressed before using the expression 'but'